Perancangan Sistem Deteksi dan Pengendalian Kebakaran Menggunakan Sensor Gas, Api, Asap, Arduino, dan Blynk - Muhammad Irfanil Hanif; Estu Sinduningrum (Journal of Information System Research (JOSH), 2025)
This study develops an Internet of Things (IoT)-based fire detection and control system with two-mode monitoring (offline and online) to provide solutions for early fire prevention and handling. The system integrates multiple sensors (MQ-2, MQ-135, and flame sensor) to detect flammable gas, smoke, and fire, and is equipped with actuators in the form of servos, fans, water pumps, and buzzers as automatic responses. Monitoring is carried out via I2C LCD for offline mode and Blynk application for online mode. The research method uses an experimental approach with stages of literature study, system design, prototype development, testing, data analysis, and improvement and optimization. The test results show that the system is able to detect fire up to a distance of 30 cm, gas with a concentration above 300 ppm, and smoke with a concentration above 200 ppm. The actuators work according to the designed programming. This system successfully integrates early detection, automatic response, and remote monitoring to provide a comprehensive solution in fire prevention and handling.